2020
DOI: 10.1073/pnas.2008213117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a brainstem locus that inhibits tumor necrosis factor

Abstract: In the brain, compact clusters of neuron cell bodies, termed nuclei, are essential for maintaining parameters of host physiology within a narrow range optimal for health. Neurons residing in the brainstem dorsal motor nucleus (DMN) project in the vagus nerve to communicate with the lungs, liver, gastrointestinal tract, and other organs. Vagus nerve-mediated reflexes also control immune system responses to infection and injury by inhibiting the production of tumor necrosis factor (TNF) and other cytokines in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 51 publications
3
79
0
Order By: Relevance
“…In optogenetic experiments, it is important to ensure that animals do not use the laser light itself as inadvertent cue to perform the task. There are several ways to exclude this possibility, such as laser stimulation without opsin expression (eYFP/mCherry control in our case), control experiments with the optical fibers disconnected, and stimulations with light that does not activate the opsins (off-wavelength control) (May et al, 2014;Kressel et al, 2020). Laser stimulation without opsin expression is the most commonly used control, since all conditions are the same except that there is no expression of opsins.…”
Section: Discussionmentioning
confidence: 99%
“…In optogenetic experiments, it is important to ensure that animals do not use the laser light itself as inadvertent cue to perform the task. There are several ways to exclude this possibility, such as laser stimulation without opsin expression (eYFP/mCherry control in our case), control experiments with the optical fibers disconnected, and stimulations with light that does not activate the opsins (off-wavelength control) (May et al, 2014;Kressel et al, 2020). Laser stimulation without opsin expression is the most commonly used control, since all conditions are the same except that there is no expression of opsins.…”
Section: Discussionmentioning
confidence: 99%
“…This effect involves a connection between vagal efferent endings and the spleen ( Rosas-Ballina et al, 2008 ), through the celiac sympathetic ganglion, inducing the release of NE by noradrenergic endings in the spleen ( Figure 2 ). They recently showed that cholinergic neurons in the DMNV, which project to the celiac superior mesenteric ganglia, significantly increase splenic nerve activity and inhibit TNF production ( Kressel et al, 2020 ). So there is a vago-sympathetic excitatory pathway while the VN and the sympathetic nervous system have generally antagonistic effects.…”
Section: Anti-inflammatory Properties Of the Vagus Nervementioning
confidence: 99%
“…Convincing evidence now exists suggesting that central RAS signaling is critical to the development of hypertension through sympathetic activation of peripheral inflammation ( de Kloet et al, 2013 ). However, convincing evidence now implicates the activation of vagal signaling in reducing the inflammatory response ( Pavlov and Tracey, 2012 ), and the DMV was recently identified as the critical brain region for the generation of this response ( Kressel et al, 2020 ). Moreover, elevated RAS signaling also increases the permeability of the blood-brain barrier ( Biancardi et al, 2014 ).…”
Section: The Influence Of Metabolic Disruptions On Parasympathetic Fumentioning
confidence: 99%